(untitled) (Ustozlar uchun, 2024)
Abstract: According to historical sources, one of the unique features of the art of playing a musical instrument was that each musician could not only play several types of musical instruments, but they were also good singers. Who also composed music. As a result, the musical activity of music-making artisans developed and led to the creation of workshops for making special musical instruments.